Optical chaotic flip-flop operations with multiple triggering under clock synchronization in the VCSEL with polarization-preserved optical injection - Zhong, Dongzhou; Yang, Guangze; Zeng, Neng; Yang, Hua; Xu, Zhe; Xi, Jiangtao (Optics express, 2020)
We investigate the evolution of nonlinear dynamic behaviors of two polarization components (x-PC and y-PC), as well as the interplay of polarization bistability and injection strength in the vertical-cavity surface-emitting laser (VCSEL) with polarization-preserved optical injection. We explore a new threshold mechanism to judge two logic outputs encoded in different dynamic behaviors of the x-PC and y-PC emitted by the VCSEL with polarization-preserved optical injection. We demonstrate implementations of two parallel optical chaotic reset-set flip-flop operations and two parallel chaotic toggle flip-flop operations that are synchronized by a clock signal and response for as short as 1 ns bit time. We further observe the reconfiguration of these two kinds of flip-flop operations with clock synchronization in different time periods by controlling the duration-time of the reset (toggle) signal with high-level. The probability of the correct trigger responses for these two kinds of flip-flop operations is controlled by the interplay of the duration-time of the reset (toggle) signal and the noise strength of the spontaneous emission. The probability that is equal to 1 for the reset-set flip-flop operations occurs in the long duration-time of the reset (toggle) signal ranging from 480 ps to 592 ps. The probability with 1 for the toggle flip-flop operations takes place in the short duration-time between 116 ps and 170 ps. Moreover, these two kinds of flip-flop operations have strong robust to the spontaneous emission noise. The optical chaotic flip-flop operation device with clock synchronization and reconfigurable trigger function proposed in our scheme offers interesting perspectives for applications where noise is unavoidable and synchronized multiple triggering is required.